ANALISIS KETERKAITAN ANTAR KELOMPOK PENGELUARAN INFLASI MENGGUNAKAN VECTOR AUTOREGRESSIVE MODEL - DIKSA, I GUSTI BAGUS NGURAH (Department of Mathematics, Universitas Negeri Gorontalo, 2021)
In this study, testing steps were carried out, namely the stationarity test, determining the optimum lag, hypothesis testing and the formation of the VAR model, the Granger causality test and classical assumptions. The data used are month to month inflation data for each inflation expenditure group in Indonesia for the period January 2013 to December 2019. The inflation expenditure group is foodstuffs; processed food, beverages, cigarettes and tobacco; housing, water, electricity, gas and fuel; clothing; health; education, recreation and sports; and transportation, communication, and financial services. However, in this study only five inflation expenditure groups were used, namely foodstuffs; processed food, beverages, cigarettes and tobacco; housing, water, electricity, gas and fuel; clothing; as well as transportation, communication and financial services. The purpose of this study is to analyze the relationship between inflation expenditure groups and to find a forecasting model for inflation expenditure groups in Indonesia. After the Granger causality test was carried out, all probability values between endogenous variables, namely the five groups of inflation expenditures were less than 0,05 or rejected H0. Therefore, it can be concluded that there is a causal relationship between endogenous variables.